Peningkatan Kreativitas Dan Kemandirian Belajar Peserta Didik Melalui Model Pembelajaran Problem Based Learning di SMP Negeri 6 Toho - Reymundus Rio; STP Reinha Larantuka; Aserie M. M. Dungus (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This Classroom Action Research was conducted in the subject of Catholic Religious Education and Character Building for Grade VII at SMP Negeri 6 Toho, Mempawah Regency, with the aim of implementing the Problem-Based Learning (PBL) model to enhance students' creativity and learning independence. This research is a Classroom Action Research (CAR) consisting of two cycles. The subjects of the research were 11 seventh-grade students. The results showed that students' creativity and learning independence in Catholic Religious Education and Character Building, through the application of the Problem-Based Learning model, in Cycle I, the category of learning independence was low, at 49.43%, and in Cycle II, it increased to 80.68%. The improvement from Cycle I to Cycle II was 31.02%, with the achievement indicator reaching ≥ 80%. Furthermore, the observation results of students' creative thinking in Cycle I showed a creativity level of 67.5%, categorized as